Mobilization of a plant transposon by expression of the transposon‐encoded anti‐silencing factor. (30th July 2013) - Fu, Yu; Kawabe, Akira; Etcheverry, Mathilde; Ito, Tasuku; Toyoda, Atsushi; Fujiyama, Asao; Colot, Vincent; Tarutani, Yoshiaki; Kakutani, Tetsuji
<x xml:space="preserve">Abstract</x> Transposable elements (TEs) have a major impact on genome evolution, but they are potentially deleterious, and most of them are silenced by epigenetic mechanisms, such as DNA methylation. Here, we report the characterization of a TE encoding an activity to counteract epigenetic silencing by the host. In Arabidopsis thaliana, we identified a mobile copy of the Mutator‐like element (MULE) with degenerated terminal inverted repeats (TIRs). This TE, named Hiun (Hi), is silent in wild‐type plants, but it transposes when DNA methylation is abolished. When a Hi transgene was introduced into the wild‐type background, it induced excision of the endogenous Hi copy, suggesting that Hi is the autonomously mobile copy. In addition, the transgene induced loss of DNA methylation and transcriptional activation of the endogenous Hi. Most importantly, the trans‐activation of Hi depends on a Hi‐encoded protein different from the conserved transposase. Proteins related to this anti‐silencing factor, which we named VANC, are widespread in the non‐TIR MULEs and may have contributed to the recent success of these TEs in natural Arabidopsis populations.